How Mandated College Students Talk About Alcohol: Peer Communication Factors Associated with Drinking. Issue 9 (1st September 2016) - Carey, Kate B.; Lust, Sarah A.; Reid, Allecia E.; Kalichman, Seth C.; Carey, Michael P.
ABSTRACT: Relatively little research has examined how peer communication influences alcohol consumption. In a sample of mandated college students, we differentiate conversations about drinking from conversations about harm prevention and provide evidence for the validity of these communication constructs. Students who violated campus alcohol policies and were referred for alcohol sanctions ( N =  345) reported on drinking patterns, use of protective behavioral strategies, perceived descriptive norms for close friends, and serving as social leader among their friends; they also reported on the frequency of conversations about drinking, about drinking safety, and about risk reduction efforts. Predicted correlations were found among types of communication and conceptually related variables. General communication was related to consumption but not protective behavioral strategies, whereas safety/risk reduction conversations correlated positively with all protective behavioral strategies. Both types of communication were associated with social leadership. Safety communication moderated the relationship between peer descriptive norms and drinks per week; more frequent talking about safety attenuated the norms–consumption relationship. Peer communication about both drinking and safety may serve as targets for change in risk reduction interventions for mandated college students.